Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/jac/dkw238
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the knowledge and attitudes regarding antibiotics and resistance (KAAR-11) questionnaire for primary care physicians

Abstract: The final 11 item KAAR questionnaire appears to be valid, reliable and responsive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Additional File 1 contains information regarding knowledge about antibiotics and resistance, and the sources of information used by students. Additional File 2 covers attitudes and beliefs, and Additional File 3 behaviour with antibiotics; in order to group the information into categories, the issues were evaluated by a panel of experts (clinical pharmacologists, psychologists, public health experts, pharmaco-epidemiologists) with experience in studies on attitudes and knowledge regarding antibiotics [ 8 , 9 ]. The categories and subcategories established are shown in Table 2 ; and, the respective studies’ results for each of the categories and subcategories established are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional File 1 contains information regarding knowledge about antibiotics and resistance, and the sources of information used by students. Additional File 2 covers attitudes and beliefs, and Additional File 3 behaviour with antibiotics; in order to group the information into categories, the issues were evaluated by a panel of experts (clinical pharmacologists, psychologists, public health experts, pharmaco-epidemiologists) with experience in studies on attitudes and knowledge regarding antibiotics [ 8 , 9 ]. The categories and subcategories established are shown in Table 2 ; and, the respective studies’ results for each of the categories and subcategories established are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…in order to group the information into categories, the issues were evaluated by a panel of experts (clinical pharmacologists, psychologists, public health experts, pharmaco-epidemiologists) with experience in studies on attitudes and knowledge regarding antibiotics [ 8 , 9 ]. The categories and subcategories established are shown in Table 2 ; and,…”
Section: Methodsmentioning
confidence: 99%
“…Questions relating to clinical factors that might influence antibiotic prescribing were based on existing guidelines for antibiotics. 2,14 Based on prior studies, [15][16][17] we included questions that addressed nonclinical factors such as patients requesting antibiotics, concern for patient satisfaction, and time pressure. We also included questions probing selfreflection of prescribing patterns relative to their peers because interventions that provide physician with audit and feedback 6 have been shown to decrease inappropriate prescribing.…”
Section: Qualitative Studymentioning
confidence: 99%
“…There are few measures which currently exist in this area. Many are specific to population sub-groups, including physicians, parents (6,(25)(26)(27), medical students (28) and pharmacists (29)(30). To our knowledge, there exists no sufficiently validated measure which aims to investigate factors influencing antibiotic use within the general populace (31).…”
Section: Introductionmentioning
confidence: 99%